Genetic Trends for Racing Performance in Turk Arabian Horses Raised - kaygisiz, ali (The Indian Journal of Animal Sciences, 2011)
The aim of this study was to estimate genetic trends on racing performance of Turkish arabian horses raised at Anatolian Agricultural farms were investigated. The effects of year on racing time and racing speed were found highly significant (P<0.01). Estimated of phenotypic trends for distances of all, 1400 m and 1600 m to -0.2841 seconds, -0.2522 seconds, -0.2415 seconds, respectively, for racing time and 0.0349 m/second, 0.0353 m/second, 0.0305 m/second, respectively, for racing seconds, respectively. All phenotypic trends were highly significant (P<0.01). Estimated of genetic trends for distances of all, 1400 m and 1600 m to -0.00749 seconds, -0.00101 seconds, -0.00546 seconds, respectively, for racing time and -0.000238 m/second, 0.00009968 m/second, 0.000564 m/second, respectively, for racing seconds. All genetic trends were insignificant (P>0.05).